Bacteria as Greenhouse Gases Reducing Agents from Paddy Plantation - MAFRIKHUL MUTTAQIN; MIFTAHUDIN .; IMAN RUSMANA (Departemen Biologi, Institut Pertanian Bogor, 2016)
High methane oxidation activity of local isolated methanotrophic bacteria have a potent as methane gases reducing agent while combined with nitrogen fixing bacteria as paddy biofertilizer. The aim of the research was to evaluate the effectiveness of the bacteria as methane gases reducing agent and biofertilizer in paddy plantation. The research was arranged in a completely randomized design consisted of fertilizer types and watering system treatments with four replicates. The research showed that paddy shoot length was not affected by the treatment. On the other hand, both plant freshand dry weight, as well as the number of productive tiller were affected by interaction of fertilizer types and watering system. Fertilizer types affected grain per panicle and methane flux after fertilization. In the end of paddy vegetative stage, bacterial fertilizers were capable to reduce methane emission in different rate. The different result in methane flux was likely due to the interaction between soil local microorganisms and soil chemical component.